Health-related quality of life and treatment preferences in adolescents with type 1 diabetes. The VIPKIDS study - Cherubini, V.; Gesuita, R.; Bonfanti, R.; Franzese, A.; Frongia, A. P.; Iafusco, D.; Iannilli, A.; Lombardo, F.; Rabbone, I.; Sabbion, A.; Salvatoni, A.; Scaramuzza, A.; et al. (Acta diabetologica, 2014)
A multi-centre, observational, cross-sectional study was carried out to determine whether the health-related quality of life (HRQOL) of adolescents with type 1 diabetes is affected by different insulin treatment systems, and which features of HRQOL are impacted by the respective insulin treatment. The study regarded 577 adolescents, aged 10–17 years, with type 1 diabetes treated with continuous subcutaneous insulin infusion (CSII) ( n = 306) or multiple daily injections (MDI) ( n = 271). The Insulin Delivery System Rating Questionnaire was validated in Italian and was self-completed by the subjects during a routine visit to the centres. Subjects were compared following the domains of the questionnaire. Good HRQOL was seen in subjects treated with either MDI or CSII. Significant differences were not found in the domains for general diabetes, including diabetes worries, social burden and psychological well-being. Multiple quantile regression analysis showed that CSII confers significant advantages in terms of HRQOL with improvements in treatment satisfaction, perceived clinical efficacy and reduction in treatment interference with daily activities. This favourable impact was more evident in subjects reporting lower HRQOL scores, suggesting that CSII may be especially useful for individuals perceiving a poor HRQOL. Analysis of the domains indicated that CSII was associated with a higher HRQOL than MDI. Life-course HRQOL evaluation using a standardised questionnaire can ensure better chronic disease management. This is particularly important when providing individualised care for adolescents, as they become increasingly responsible for managing their diabetes.